DETERMINAN PENAWARAN CABAI MERAH DI SUMATERA UTARA - Rahmanta; Elisabet Siahaan; Lindawati; Abid Raif Rahmatullah; Edi Warsito (Fakultas Pertanian Universitas Janabadra, 2026)
The increasing demand for red chili peppers has led to a significant increase in their market circulation. The fluctuating price of red chili peppers encourages farmers to produce larger or smaller quantities of this commodity in the following season. The yield of the harvest will affect the amount of production offered, while supply will affect the price. This study was conducted to analyze the factors that influence the supply of red chili peppers. The method used in this study was quantitative research, and the data used in this study was time series data from 2020 to 2024 on a monthly basis, resulting in 60 observations. The model used was multiple linear double log regression analysis. The results of the study show that partially and simultaneously, the price of red chili peppers, the price of urea fertilizer, the price of ZA fertilizer, the price of TSP fertilizer, the area of harvested land, and labor wages significantly affect the supply of red chili peppers.